The Decision on the "Optimal" Human Pluripotent Stem Cell. (1st April 2014) - Rosner, Margit; Schipany, Katharina; Hengstschläger, Markus
Abstract : The array of human pluripotent stem cells now includes embryonic stem cells, induced pluripotent stem cells, and amniotic fluid stem cells. This article compares several aspects of these stem cell types and highlights the need for future appropriate methodological management to include a decision on the "optimal" stem cell to use for a specific application. Summary: Because of recent advances, the array of human pluripotent stem cells now contains embryonic stem cells, derived from "surplus" in vitro fertilization embryos or from cloned embryos; induced pluripotent stem cells; and amniotic fluid stem cells. Here, we compare these stem cell types regarding ethical and legal concerns, cultivation conditions, genomic stability, tumor developing potentials, and applicability for disease modeling and human therapy. This overview highlights that in the future appropriate methodological management must include a decision on the "optimal" stem cell to use before the specific application